Sensing that Something is Wrong: On the Role of Senses in Sensemaking in Frontline Safety Work - Midtlyng Grethe (Journal of Organizational Sociology)
Based on an ethnography of work in a high-security prison, this article explores how safety practitioners develop specialised sensing skills through close engagement with their socio-material work environment and how they use these skills in constructing their understandings of what is going on in everyday work. The results make visible the potential role of the senses in how workers keep systems running, how they maintain safety in situations where quick reactions are needed and for the fast transition to more deliberate forms of sensemaking for early intervention. However, despite the importance prison officers ascribed to the use of the senses for their ability to work proactively, certain technologies seemed to reduce access to sensory inputs and thereby the ability to notice weak signals. This indicate challenges regarding embodied and tacit safety knowledge when more visible representations of safety are implemented. The article aims to contribute to a theoretical framework for understanding the role of senses in safety work through the concept of sensemaking as an embodied, socio-material process.